Boosting taxes for boasting about houses: Status concerns in the housing market - Johannes Schünemann; Timo Trimborn (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
There is empirical evidence that households use residential houses as status goods. Their visibility qualifies them as an excellent signaling device of the relative income and wealth position, in contrast to less visible financial assets. To this end we introduce a residential housing sector and status concerns for housing into a neoclassical framework. In the model, households derive utility from the absolute amount of housing and from comparing their stock of housing to a reference stock, which is composed of the current or past level of housing of their peers. We analyze how status concerns affect household behavior and find that they increase housing demand and labor supply. Furthermore, we find that status concerns exert a negative externality and elevate housing to inefficiently high levels. We derive a (state contingent) optimal tax that establishes the first-best allocation along the transition path and at the steady state. Calibrating the model to the US we quantify the optimal tax on residential housing to 1.8%. Introducing the optimal tax entails a considerable welfare gain of 0.29% measured in consumption equivalents.
Keywords: E03; O10; D10; H21; R31; 330; Status Concerns; Residential Housing; Optimal Taxation